KORELASI RADIASI DAN LAMA PENYINARAN MATAHARI TERHADAP PERTUMBUHAN DAN PRODUKSITANAMAN SORGUM (Sorghum bicolor L. Moench) - Tania, Putri; Iswahyudi; Sutarni; Juanda,, Boy Riza; Azis, Abdul (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
This study aims to investigate the T-test, F-test, and correlation test of radiation and duration of sunlight exposure on the growth and production of sorghum plants. The research was conducted at the Meteorology, Climatology, and Geophysics Agency (BMKG) Climate Station in Indrapuri, Aceh Besar, from March to June 2023.The study employed Multiple Linear Regression Analysis, T-test, F-test, Correlation Coefficient, and Determination Coefficient. The results indicate that radiation and duration of sunlight exposure significantly affect plant height, number of leaves, and sorghum production. Regression analysis also shows that radiation and duration of sunlight exposure have a significant impact on all parameters studied. The T-test reveals that radiation does not have a partial effect on plant height and the number of leaves, but it does have a partial effect on weight and wet weight. On the other hand, the duration of sunlight exposure has a partial effect on plant height and the number of leaves, but it does not have a partial effect on the wet weight of samples and the wet weight. The simultaneous F-test analysis shows that radiation and duration of sunlight exposure have a simultaneous effect on plant height. Correlation analysis shows that plant height, number of leaves, wet weight per sample, and wet weight per plot are related.